2003
DOI: 10.1097/01.mp.0000081051.55284.2a
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Vulvar and Vaginal Intraepithelial Neoplasia: Correlation of Histologic Features with Human Papillomavirus DNA Detection and MIB-1 Immunostaining

Abstract: Histologic criteria of low-grade vulvar/vaginal intraepithelial neoplasia (VIN1/VAIN1) are well established; however, a significant interobserver variability in diagnosing VIN1/VAIN1 has been reported. The goal of this study was to evaluate the utility of MIB-1 immunostaining as an adjunct test to increase the diagnostic accuracy in equivocal cases of VIN1/VAIN1. The second goal was to examine the distribution of low-and high-oncogenic risk human papillomaviruses (HPVs) in VIN1/VAIN1 lesions. Consecutive vulva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 21 publications
3
28
1
4
Order By: Relevance
“…A previous study reported that 84% of VAIN 1 lesions were associated with HR HPV DNA. 14 In this study, we found that 74.3% of VAIN 1, 85.7% of VAIN 2 and 100% of VAIN 3 lesions were associated with HR HPV DNA.…”
Section: Discussionmentioning
confidence: 62%
“…A previous study reported that 84% of VAIN 1 lesions were associated with HR HPV DNA. 14 In this study, we found that 74.3% of VAIN 1, 85.7% of VAIN 2 and 100% of VAIN 3 lesions were associated with HR HPV DNA.…”
Section: Discussionmentioning
confidence: 62%
“…8,16 Therefore, we used Ki-67 for supporting diagnosis of VAIN, where Ki-67 staining was positive in 98.8% of the VAIN samples. Logani et al 12 included only HPV-positive cases as confirmed cases of VAIN (n ¼ 18), which resulted in 100% HPV positivity. Two other series (n ¼ 74, 111) reported similar lower HPV positivities, 82.4% and 83%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 immunohistochemical staining was performed to support the histological diagnosis especially for VAIN1. 12 The tissue array for each formalin-fixed, paraffin-embedded specimen was subjected to autoclave antigen retrieval at 121 C for 10 min in Trilogy TM (Cell Marque, Rocklin, CA) and incubated in an automated stainer (Ventana Medical Systems, Tucson, AZ). A Ki-67 mouse monoclonal antibody (Dako, Carpinteria, CA) was used at a dilution of 1:100, and the samples were stained with diaminobenzidine chromogen and counterstained with hematoxylin.…”
Section: Ki-67 Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations